Gestión administrativa y su aporte en el ejercicio profesional de las secretarias en la agencia Banco Pichincha Vinces - Cedeño Cedeño, Leonela Imalay (2020)
The present case study has as its theme: Administrative management and its contribution in the professional practice of secretaries and was carried out at the Banco Pichincha = Vinces Agency, which is a company whose purpose is to infuse and reward by offering quality service, For the development of this case study was used the deductive method that allowed to obtain general information through a survey that was carried out which allowed to collect important and precise information. The objective is to know whether the secretaries have the capacity to function in the professional field and to determine how the administrative management contributes in their professional practice. The survey that was carried out resulted in the Banco Pichincha Agency- Vince’s secretaries do not have the knowledge of the administrative area so they do not have the capacity to develop or the skills to provide a good service for both the company and the users. Therefore there is a lack of conformity and the administrative processes are not exactly carried out so they do not have the knowledge to be able to execute them in the correct way since it has been confirmed that it is important for the secretaries to know from the administrative so that they can perform effectively.